Estimation of stature from head circumference in Gujarati adolescent population - Shah K Ritesh; Sanjay Kumar D Kanani; Patel P Jitendra; Nirvan B Ashok; Patel G Bharat (Wolters Kluwer Medknow Publications, 2017)
Background & aims: Establishing personal identity is one of prime objective in forensic investigation especially when the body is mutilated or certain body parts are missing. Height estimation is one of the main parameter in establishing the identity of the deceased and head circumference can be used to correctly estimate the height. Aim of current study was to establish anthropometric correlation of stature with head circumference in Gujarati adolescent population. Materials and Methods: 150 asymptomatic, apparently healthy, adolescent and adult medical students with age between 18 to 22 years belonging to various regions of Gujarat were selected. Head circumference and height of subjects were measured using a non-stretchable measuring tape in erect posture. Obtained data were analysed by regression analysis to derive regression equations for estimation of stature from head circumference. Results: We were able to calculate mean and SD of stature and head circumference, correlation coefficient and regression coefficient between head circumference and stature. We also derived the regression equations in order to estimate the stature from the head circumference. Conclusion: In the present study, we found that there is strong positive correlation between stature and head circumference. The regression equations obtained from the data can be used correctly to estimate the stature from the head circumference in Gujarati adolescent population.